2018
DOI: 10.5194/os-14-259-2018
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of oceanic subsurface mixing under a severe cyclonic storm using a coupled atmosphere–ocean–wave model

Abstract: Abstract. A coupled atmosphere-ocean-wave model was used to examine mixing in the upper-oceanic layers under the influence of a very severe cyclonic storm Phailin over the Bay of Bengal (BoB) during 10-14 October 2013. The coupled model was found to improve the sea surface temperature over the uncoupled model. Model simulations highlight the prominent role of cyclone-induced near-inertial oscillations in subsurface mixing up to the thermocline depth. The inertial mixing introduced by the cyclone played a centr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Thus, in order to account for the oceanic response in the Sargasso Sea, we restricted the study area to the deep waters to the right of Dorian's trajectory. Given that upwelling, cooling, and deepening of the isothermal layer are more intense on the right side of a TC's trajectory in the Northern Hemisphere (Price, 1981;Hanshaw et al, 2008;Gierach and Subrahmanyam, 2008;Fu et al, 2014), our asymmetric approach captures the strongest oceanic response. In addition to these Lagrangian measurements along Dorian's trajectory, we also investigated the oceanic response in a square area (Eulerian) located to the right of its trajectory (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in order to account for the oceanic response in the Sargasso Sea, we restricted the study area to the deep waters to the right of Dorian's trajectory. Given that upwelling, cooling, and deepening of the isothermal layer are more intense on the right side of a TC's trajectory in the Northern Hemisphere (Price, 1981;Hanshaw et al, 2008;Gierach and Subrahmanyam, 2008;Fu et al, 2014), our asymmetric approach captures the strongest oceanic response. In addition to these Lagrangian measurements along Dorian's trajectory, we also investigated the oceanic response in a square area (Eulerian) located to the right of its trajectory (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…3b and c). TCs typically give rise to upwelling flow underneath the storm centre and weak downwelling of the displaced warm water over a broad area beyond the upwelled regions (Price, 1981;Jullien et al, 2012;Fu et al, 2014). Overall, TC-induced upwelling by Ekman pumping plays a major role in inducing cooling under the TC centre (e.g.…”
Section: Ocean Cooling and Its Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors found that during and immediately following a cyclone's passage, the spatially averaged MLD in the Sargasso Sea increases sharply by 7 m on average, while the positive anomaly rapidly diminishes during the subsequent days. Then, after the post-storm shoaling of the MLD, it can oscillate (shoaling/deepening) around the same mean depth (Foltz et al, 2015;Zhang et al, 2016;Prakash et al, 2018). However, this temporal evolution considers the oceanic response to an individual TC.…”
Section: Prementioning
confidence: 99%
“…Although strong mixing due to TCs is mostly confined to the upper ocean, the cyclone-induced inertial waves affect the subsurface mixing too (Prakash et al, 2018). Part of the energy transferred to inertial currents by the storm may propagate below the mixed layer and finally drive turbulent mixing in the thermocline (Cuypers et al, 2013).…”
Section: Chlorophyll-a Concentration Bloommentioning
confidence: 99%